CARBONATE MINERAL SOLUBILITY AT LOW TEMPERATURES IN THE NA-K-MG-CA-H-CL-SO4-OH-HCO3-CO3-CO2-H2O SYSTEM - Marion G.M. (My University, 2001)
Carbonate minerals have played an important role in the geochemical evolution of Earth, and may have also played an important role in the geochemical evolution of Mars and Europa. Several models have been published in recent years that describe chloride and sulfate mineral solubilities in concentrated brines using the Pitzer equations. Few of these models are parameterized for subzero temperatures, and those that are do not include carbonate chemistry. The objectives of this work are to estimate Pitzer-equation bicarbonate-carbonate parameters and carbonate mineral solubility products and to incorporate them into the FREZCHEM model to predict carbonate mineral solubilities in the Na-K-Mg-Ca-H-Cl-SO4-OH-HCO3-CO3-CO2-H2O system at low temperatures (=<25°C) with a special focus on subzero temperatures.Most of the Pitzer-equation parameters and equilibrium constants are taken from the literature and extrapolated into the subzero temperature range. Solubility products for 14 sodium, potassium, magnesium, and calcium bicarbonate and carbonate minerals are included in the model. Most of the experimental data are at temperatures =< -8°C; only for the NaHCO3-NaCl-H2O and Na2CO3-NaCl-H2O systems are there bicarbonate and carbonate data to temperatures as low as -21.6°C.In general, the fit of the model to the experimental data is good. For example, calculated eutectic temperatures and compositions for NaHCO3, Na2CO3, and their mixtures with NaCl and Na2SO4 salts are in good agreement with experimental data to temperatures as low as -21.6°C. Application of the model to eight saline, alkaline carbonate waters give predicted pHs ranging from 9.2 to 10.2, in comparison with measured pHs that range from 8.7 to 10.2. The model suggests that the CaCO3 mineral that precipitates during seawater freezing is probably calcite and not ikaite. The model demonstrates that a proposed salt assemblage for the icy surface of Europa consisting of highly hydrated MgSO4 salts and natron (Na2CO3 . 10H2O) is an incompatible salt assemblage.